Does This Adult Patient Have a Blunt Intra-abdominal Injury? - Daniel K. Nishijima; David L. Simel; David H. Wisner; James F. Holmes (2012)
Blunt abdominal trauma often presents a substantial diagnostic challenge. Well-informed clinical examination can identify patients who require further diagnostic evaluation for intra-abdominal injuries after blunt abdominal trauma.To systematically assess the precision and accuracy of symptoms, signs, laboratory tests, and bedside imaging studies to identify intra-abdominal injuries in patients with blunt abdominal trauma.We conducted a structured search of MEDLINE (1950-January 2012) and EMBASE (1980-January 2012) to identify English-language studies examining the identification of intra-abdominal injuries. A separate, structured search was conducted for studies evaluating bedside ultrasonography.We included studies of diagnostic accuracy for intra-abdominal injury that compared at least 1 finding with a reference standard of abdominal computed tomography, diagnostic peritoneal lavage, laparotomy, autopsy, and/or clinical course for intra-abdominal injury. Twelve studies on clinical findings and 22 studies on bedside ultrasonography met inclusion criteria for data extraction.Critical appraisal and data extraction were independently performed by 2 authors.The prevalence of intra-abdominal injury in adult emergency department patients with blunt abdominal trauma among all evidence level 1 and 2 studies was 13% (95% CI, 10%-17%), with 4.7% (95% CI, 2.5%-8.6%) requiring therapeutic surgery or angiographic embolization of injuries. The presence of a seat belt sign (likelihood ratio [LR] range, 5.6-9.9), rebound tenderness (LR, 6.5; 95% CI, 1.8-24), hypotension (LR, 5.2; 95% CI, 3.5-7.5), abdominal distention (LR, 3.8; 95% CI, 1.9-7.6), or guarding (LR, 3.7; 95% CI, 2.3-5.9) suggest an intra-abdominal injury. The absence of abdominal tenderness to palpation does not rule out an intra-abdominal injury (summary LR, 0.61; 95% CI, 0.46-0.80). The presence of intraperitoneal fluid or organ injury on bedside ultrasound assessment is more accurate than any history and physical examination findings (adjusted summary LR, 30; 95% CI, 20-46); conversely, a normal ultrasound result decreases the chance of injury detection (adjusted summary LR, 0.26; 95% CI, 0.19-0.34). Test results increasing the likelihood of intra-abdominal injury include a base deficit less than -6 mEq/L (LR, 18; 95% CI, 11-30), elevated liver transaminases (LR range, 2.5-5.2), hematuria (LR range, 3.7-4.1), anemia (LR range, 2.2-3.3), and abnormal chest radiograph (LR range, 2.5-3.8). Symptoms and signs may be most useful in combination, particularly in identification of patients who do not need further diagnostic workup.Bedside ultrasonography has the highest accuracy of all individual findings, but a normal result does not rule out an intra-abdominal injury. Combinations of clinical findings may be most useful to determine which patients do not require further evaluation, but the ideal combination of variables for identifying patients without intra-abdominal injury requires further study.